LITERATURE REVIEW ON MISUSE OF OTC DRUGS IN THE COMMUNITY: PATTERNS, CAUSES, AND SOLUTIONS - Khairunnisa Azani Meilinasary; Mathla'il Fajri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to systematically examine the misuse of over-the-counter (OTC) drugs in the community based on national and international research published between 2020 and 2025. A qualitative literature review was conducted by thematically analyzing 15 relevant scientific articles. The findings indicate common misuse patterns, including consumption without medical indication, overdose, long-term use, and neglect of side effects or drug interactions. The contributing factors are multifactorial, such as low medication literacy, misleading advertisements, misconceptions about OTC safety, and inadequate pharmacist supervision. On the other hand, proposed solutions include community-based educational approaches, redesign of pharmacy systems, and the utilization of digital health technologies such as telepharmacy. These findings highlight the urgent need for integration of public education, regulation, and service innovation to reduce the risk of OTC misuse.